1969
DOI: 10.1037/h0028622
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of rater-ratee acquaintance in the validity and reliability of ratings.

Abstract: Unacquainted Se worked in three-man groups under relevant (mathematical tasks) and irrelevant (socializing) acquaintance conditions. The Ss rated one another OB scales that defined several cognitive skills, They were also rated on these same scales by observers who were dependent on visual information, exclusively, and were unacquainted with the group members or the specific nature of the tasks being performed. As hypothesized, group members under the relevant acquaintance condition achieved consistently good … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
2

Year Published

1982
1982
2010
2010

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 9 publications
0
23
2
Order By: Relevance
“…Above this level, validity was stable and almost did not change as interrater correlation increased. This finding, together with other studies (Borman, 1975;Buckner, 1959;Freeberg, 1969;Weekley & Gier, 1989), cast doubt on the assertion that interrater correlation in the field of performance rating is a proper measurement of reliability.According to classical measurement theory, validity and reliability are related. Cronbach (1970) stated, "The error portion of the test score will not correlate with any criterion.…”
contrasting
confidence: 55%
“…Above this level, validity was stable and almost did not change as interrater correlation increased. This finding, together with other studies (Borman, 1975;Buckner, 1959;Freeberg, 1969;Weekley & Gier, 1989), cast doubt on the assertion that interrater correlation in the field of performance rating is a proper measurement of reliability.According to classical measurement theory, validity and reliability are related. Cronbach (1970) stated, "The error portion of the test score will not correlate with any criterion.…”
contrasting
confidence: 55%
“…Another study found that ratings made by acquainted raters of briefings on research projects were more accurate than those made by unacquainted raters (Van Scotter, Moustafa, Burnett, & Michael, 2007). Freeberg (1969) found that performance ratings were more valid when raters possessed task-relevant acquaintance with the ratee than when they possessed merely task-irrelevant acquaintance (e.g., socializing). Kingstrom and Mainstone (1985) found that ratees with whom supervisors had established relatively high task acquaintance (familiarity with the employee's job behavior) and personal acquaintance received more favorable performance ratings than other ratees.…”
Section: Rater Expectations About the Rateementioning
confidence: 97%
“…The first six scales were designed to assess the kinds of reasoning skills that emerged from the factor analysis of faculty ratings of the importance of various reasoning skills and are described in Table 2. In addition, a seventh scale was included to obtain an indication of each rater's familiarity with each student, since familiarity is likely to affect the quality of ratings and therefore the relationship of ratings to test performance (Freeberg, 1969;Landy & Farr, 1980). Moreover, the importance of obtaining some indication of raters' acquaintance with ratees has been reinforced recently in the new Standards for Educational and Psychological Testing (AERA, APA, NCME, 1985), which state that when criteria are composed of rater judgments, the degree of knowledge that raters have concerning ratee performance should be reported.…”
Section: Methods Instrument Developmentmentioning
confidence: 99%
“…Previous research has suggested that the nature of raters' contact with ratees may affect the quality of ratings, hence their relationship to other variables (e.g., Freeberg, 1969;Landy & Farr, 1980). In providing their ratings in this study, faculty were also asked to describe how much opportunity (significantly less, slightly less, neither more nor less, slightly more, or significantly more compared with other students) they had to observe/judge the extent to which the students they rated possessed the kinds of analytical skills of interest.…”
Section: Role Of Faculty Familiarity With Studentsmentioning
confidence: 99%